Tourism Attractiveness in Improving Re-visit Decisions through the Destination Image, Accessibility and Word of Mouth - Nanini Diva Malinka; Darwin Raja Unggul Saragih (CV. ULIL ALBAB CORP, 2023)
This study aims to determine the impact of destination image, accessibility, and word-of-mouth on local and international tourists' decision to revisit the Bogor Zoological Museum. For the study's analysis, 250 individuals who had visited the Bogor Zoological Museum on multiple occasions were selected at random and assigned a number. The data collection method is a Likert-scale questionnaire. This analysis employs multiple linear regression with SPSS version 25 to conduct validity tests, reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, linearity tests, t-tests, f-tests, and coefficient and determination analysis. The decision to revisit the Bogor Zoological Museum is significantly influenced by the destination's image, its accessibility, and positive word-of-mouth, according to research.